2023
DOI: 10.18280/mmep.100105
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Production Lines in a Manufacturing Company Using Data Envelopment Analysis (DEA)

Abstract: The concept of producing more output(s) with less input(s) has always been one of the goals of every manufacturing industry. However, continuous evaluation of production systems will ensure that production targets are not only being met but also to ensure that each decision-making unit produces at an optimal level compared to the laid down standard(s). This work evaluated the efficiency of the six most productive production lines in a brewery plant using one of the non-parametric efficiency measurement techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Additionally, it was reported from different research studies that biodiesel or blends in CI engines have shown reduced trends in noise pollution and good noise quality [19][20][21][22][23][24][25][26][27]. Moreover, renewable fuels derived from vegetable oils have suitable engine performance, in other operations, some fuels can reduce performance, high carbon and lacquer deposition, and cause of engine damage [28][29][30][31]. Deposition around the injector tip is due to high temperatures owing to the advanced diesel injection system [31][32][33][34].…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Additionally, it was reported from different research studies that biodiesel or blends in CI engines have shown reduced trends in noise pollution and good noise quality [19][20][21][22][23][24][25][26][27]. Moreover, renewable fuels derived from vegetable oils have suitable engine performance, in other operations, some fuels can reduce performance, high carbon and lacquer deposition, and cause of engine damage [28][29][30][31]. Deposition around the injector tip is due to high temperatures owing to the advanced diesel injection system [31][32][33][34].…”
Section: Background and Literature Reviewmentioning
confidence: 99%